Successful treatment of liver metastasis from solid pseudopapillary tumor of the pancreas: a case report - Liu, Taiguo; He, Jianping; Cao, Dan; Huang, Ying (Contemporary Oncology/Współczesna Onkologia, 2013)
Solid pseudopapillary tumor of the pancreas is a rare pancreatic neoplasm that typically occurs in young females. As a low-grade malignancy, the tumor seldom recurs and metastasizes. Management of liver metastasis from such a tumor remains unclear. We present a case of a young girl with liver metastasis due to solid pseudopapillary tumor of the pancreas. She was admitted with chief complaints of epigastric mass on palpation for 16 months and upper abdominal pain for 2 months. An abdominal CT scan detected a mass in the pancreas and multiple nodules in the liver. Then, percutaneous CT-guided tru-cut biopsy was performed and pathological diagnosis of the biopsy material revealed solid pseudopapillary tumor of the pancreas. At 3 months after surgical resection of the pancreatic and liver tumors, CT scan found nodules in her liver. The patient received treatment with transcatheter arterial chemoembolization. She remained well during the 3 years of follow-up with no evidence of recurrence. Therefore, it is suggested that although solid pseudopapillary tumor of the pancreas may be associated with malignant potentiality, a favorable prognosis can also be obtained via rigorous treatment.